THE ANALYSIS OF TAXATION SOCIALIZATION ACTIVITIES TO INCREASE COMPLIANCE OF INDIVIDUAL TAXPAYERS AT KPP PRATAMA JEMBER IN 2021 - Velati, Adhelvia; Pudjolaksono, Drs. Eko (jfpublisher, 2023)
The tax socialization activity is one of the efforts to make it easier for the public to calculate, pay and report taxes at KPP Pratama Jember, which includes tax classes, seminars, and workshops and conducts outreach activities through social media such as Instagram. This research aims to discover the socialization activities carried out by KPP Pratama Jember in increasing taxpayer compliance, the effectiveness of these socialization activities, the obstacles encountered, and the impact of these socialization activities. This study used a qualitative descriptive method with primary data from interviews with KPP Pratama Jember officials. The data used in this study is data for 2021. The results of this study indicate that KPP Pratama Jember has programs related to tax socialization, referred to as Tax Education. This program consists of two program models: routine and incidental or thematic. There are obstacles faced by KPP Pratama Jember, namely internal obstacles and external obstacles. The effectiveness of the socialization program at KPP Pratama Jember towards taxpayer compliance is quite effective. The impact of the socialization program at KPP Pratama Jember on taxpayer compliance is excellent.